2021
DOI: 10.11622/smedj.2019168
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of trampoline-related injuries presenting to a paediatric emergency department in Singapore

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…14 Several studies in areas worldwide show similar trends in injury presentation from trampoline use, with extremity injuries being most prevalent. [11][12][13]15 These results indicate the danger of trampoline use in children and highlight the most frequent injuries seen in this population. The majority of patients in our cohort with trampoline injuries presented with injury to an extremity (84.1%), while the remaining 15.9% of patients had an injury classified as "other."…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…14 Several studies in areas worldwide show similar trends in injury presentation from trampoline use, with extremity injuries being most prevalent. [11][12][13]15 These results indicate the danger of trampoline use in children and highlight the most frequent injuries seen in this population. The majority of patients in our cohort with trampoline injuries presented with injury to an extremity (84.1%), while the remaining 15.9% of patients had an injury classified as "other."…”
Section: Discussionmentioning
confidence: 85%
“…Trampoline use is not unique to the United States of America; some of the locations in which trampoline-related injuries have been studied are Australia, 11 Singapore, 12 France, 13 and Austria. 14 Several studies in areas worldwide show similar trends in injury presentation from trampoline use, with extremity injuries being most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, trampolining requires a combination of several components, such as strength, body stability, muscle coordination, and spatial integration [6], parameters which are negatively affected in older individuals [31][32][33]. Moreover, even though trampoline use has standard safety measures such as padded frames [14], inexperienced adult users may choose not to follow safety instructions-potentially leading to serious injury [14,17]. On the other hand, it has been clearly demonstrated that mini-trampoline exercise may improve dynamic stability and balance ability in older persons by increasing the strength of plantar flexor muscles and the ability to regain balance during forward falls [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, trampolining also has downsides, as shown by studies on trampolining accidents in children [3,4,[7][8][9][10][11][12][13]. Indeed, several studies demonstrate that there has been an increase in the incidence of trampoline-related injuries in children in recent decades [14]. Although the majority of injuries are minor, approximately 10% of all paediatric trampolineassociated injuries are severe [8], which can ultimately lead to major functional disability such as paraplegia and quadriplegia or even death [1,7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A vast majority of patients sustained the injury during recreational activities and among our recorded mechanisms of injury fall from trampolines and climbing frames were major contributing factors. Some previous literature has advocated the introduction of parent education, parental supervision, and safety measures such as use of rubber surfacing in playgrounds to reduce the incidence of such injuries [17][18][19][20]. Four percent patients had a neurological deficit as a result of the fracture, and all of these were neurapraxias that resolved with conservative management for the nerve injury.…”
Section: Discussionmentioning
confidence: 99%